Freshwater macroalga, Ulva pilifera (Ulvaceae, Chlorophyta) as an indicator of the trophic state of waters for small water bodies - Andrzej S. Rybak (Elsevier, 2021)
Mass occurrence of green algae of the genus Ulva in the form of algal blooms (known as “green tides”) is often associated with high concentrations of biogens in the water. Therefore, Ulva species are most often used in monitoring seawater trophy and far less frequently freshwater trophy. In Europe, the biomonitoring of river ecosystems is based on aquatic plants. According to the River Macrophyte Index (RMI), river populations of Ulva macroalgae (only tubular Enteromorpha-like Ulva) are considered good indicators for eutrophic waters. This paper analyses the legitimacy of using U. pilifera as a trophy indicator in the case of ponds. It has been noted that freshwater populations of U. pilifera are much more common in lakes, dammed reservoirs, or ponds than in rivers. In this study, analysed populations of U. pilifera originated from 14 ponds located in central Poland. Data analysis relied on the Carlson Trophic State Index (CTSI), which was compared with other known trophic indices. According to CTSI values, U. pilifera was most common in eutrophic ponds, where the mean concentrations of ammonium nitrogen, nitrates, total phosphorus, and chlorophyll a reached 581, 241, 212, and 20 µg·L−1, respectively. The results indicate that U. pilifera can be considered a bioindicator for eutrophic waters (50–70 of CTSI). It would therefore be appropriate to introduce U. pilifera as part of biomonitoring conducted in small bodies of water. Major arguments in favour of practical application of U. pilifera are: (i) it is a large macroalga, the thalli of which can reach a length of > 1.0 m, (ii) it is an easy-to-identify species; even by non-experts (it is characterized by a distinctive tubular shape of the thallus), and (iii) it occurs in bulk in conditions of eutrophy, creating an easily observable bloom.